The Peking Health Anxiety Scale for Infectious Diseases: psychometric properties and short-form development - Feng, Junkai; Wang, Yixuan; Zang, Yinyin (Frontiers in Psychiatry, 2026)
BackgroundHealth anxiety can escalate rapidly during infectious disease outbreaks, yet existing assessment tools lack specificity for such contexts. This study aimed to develop and validate the Peking Health Anxiety Scale for Infectious Diseases (PHAID), a brief, context-sensitive measure tailored to infectious disease-related health anxiety.MethodsThe PHAID was adapted from the Short Health Anxiety Inventory, with items revised to focus on COVID-19. Psychometric validation was conducted in a sample of 1,660 adults recruited primarily from the United States via Amazon’s MTurk during the COVID-19 pandemic. Factor structure was determined using exploratory and confirmatory factor analyses. Reliability, convergent and discriminant validity, and test–retest stability were assessed. A clinical cutoff and the relationship with preventive behaviors were examined. A 5-item short form (PHAID-S) was developed using Item Response Theory.ResultsThe PHAID demonstrated a stable two-factor structure (Catastrophic Thinking and Infection Worries), excellent internal consistency (α = 0.931 and ω = .947), good test–retest reliability (r = 0.83), and strong convergent and discriminant validity. PHAID scores showed a cubic relationship with handwashing frequency, distinguishing adaptive vigilance from excessive behaviors. The PHAID-S retained good reliability (α = 0.85) and screening accuracy. The cutoff scores were 24 for PHAID and 11 for PHAID-S.ConclusionsThe PHAID and its short form provide reliable and valid tools for identifying infectious disease-related health anxiety. They show promise for supporting research and public health screening during outbreaks, though further validation in more diverse populations and clinical settings is warranted.